82 Virtual Reality Home Visit Simulation: Pilot Study. (6th February 2020) - Bell, C; Mellows, C; Rogans-Watson, R; May-Miller, H; Heitz, E
Abstract: Introduction: There are multiple drivers to move healthcare into community settings, including people's own homes. Traditional healthcare training, particularly medical training, is largely hospital-based, and hospital-based models of care. Few professions have explicit training in how best to assess an individual at home, and the additional elements to examine when visiting an induvial in their own home. To meet this training need Croydon Health Services were successful in a bid for funding to develop training to meet this gap. With this funding, a programme was developed and after attempts at simulation home visits in the simulation centre, a virtual reality (VR) home visit scenario was devised and filmed in the community using a professional actor to simulate a housebound individual. The recording was then professionally edited by a specialist VR team to maximise its effectiveness including interactive educational elements. Methods: A pilot study examining the acceptability of the virtual reality home visit scenario was designed. A user group of medical staff with limited community experience participated in undertaking the virtual reality scenarios, delivered via Samsung Note 8 devices combined with Samsung Gear VR headsets. Feedback was received from participants by standardised paper-based surveys. Results: 7 responses were obtained. 100% of respondents described the scenario as easy to use, as well as agreeing that the same experience could not be gained from watching a standard video of the same scenario. 100% of respondents felt that the on-screen information was helpful. Feedback on areas for improvement suggested a desire for greater interactivity of other aspects of home assessment, and a desire to improve interactivity with the simulated patient, including history taking. Conclusions: Virtual reality home visit simulations are an acceptable and effective tool to introduce new concepts to staff. Further development should aim to maximise interactivity in the scenario and explore options for greater interaction with the simulated patient. Further role out of the virtual reality is planned for local and regional training sessions.